PELATIHAN COPYWRITING UNTUK GENERASI HUSTLING - I Gusti Agung Sri Rwa Jayantini; Putu Desi Anggerina Hikmaharyanti; Ni Made Verayanti Utami; Ni Nyoman Deni Ariyaningsih; I Dewa Ayu Salsa Bila Ninda Pradevi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
Digital transformation has been sounding since 2021 and massive improvement is still being conducted after the outbreak. The transformation cannot be separated from the use of language as the media in linking the demand and supply, given that copywriting skill is urgently needed as many people enjoy content. By organizing workshop on copywriting skill, the goal of supporting side hustler to get the opportunity in this field was gratefully achieved. A day workshop collaborated with Badan Kreatif Denpasar (Denpasar Creative Agency) has raised the confidence of youth as the target to elicit their passion in copywriting. The impact of the workshop is positively encouraging the youth passion in having remote working as their dominant personality trait.